Evaluation of Diaphragmatic Function after Interscalene Block with Liposomal Bupivacaine: A Randomized Controlled Trial. (21st January 2022) - Berg, Aaron A.; Flaherty, James M.; Habeck, Jason M.; Harrison, Alicia K.; Braman, Jonathan P.; Kaizer, Alexander M.; Hutchins, Jacob L.
Abstract : Background: Interscalene blocks provide analgesia for shoulder surgery but also cause phrenic nerve paralysis. Liposomal bupivacaine is approved for use in interscalene blocks with the potential to provide longer pain control. However, the impact of liposomal bupivacaine on the phrenic nerve has not been evaluated. It was hypothesized that patients who received an interscalene block with both bupivacaine and liposomal bupivacaine would have a decreased diaphragmatic excursion when compared to bupivacaine alone at 24 h. Methods: This was a double-blinded study of adult patients who were randomized to receive an interscalene block with either 20 ml 0.5% bupivacaine (bupivacaine group) or 10 ml 0.5% bupivacaine plus 10 ml liposomal bupivacaine (liposomal bupivacaine group). Twenty-six patients were randomized with 22 included in the analysis. Diaphragmatic excursion ( via ultrasound) and spirometry were assessed before the block, in the postanesthesia care unit, and at 24 h postblock. The primary outcome was diaphragm excursion with sigh. No adverse events were observed. Results: At 24 h, the liposomal bupivacaine group median [25th, 75th], had a greater percent change in diaphragmatic excursion during sigh breath compared to the bupivacaine group, –24% [–30, –9] versus 9% [–8, 26], difference in location, 32 (95% CI, 12 to 52), P = 0.007. Five patients in the liposomal bupivacaine group had a greater than 25% reduction in diaphragmatic excursion at 24 h versus zero in the bupivacaine group. They also had a significantly greater percent reduction in forced expiratory volume in 1 s and forced vital capacity compared with the bupivacaine group at 24 h (median decrease of 22% vs . 2%, P = 0.006, and median decrease of 19% vs . 1%, P = 0.049, respectively). Conclusions: The addition of liposomal bupivacaine to bupivacaine in an interscalene block results in statistically significant reductions in diaphragm excursion and pulmonary function testing 24 h after block placement when compared to bupivacaine alone. This reduction, however, falls within the range of normal diaphragmatic function. Abstract : Patients undergoing shoulder surgery received interscalene blocks using plain bupivacaine versus a mixture of plain and liposomal bupivacaine. At 24 h, those receiving liposomal bupivacaine had greater reductions in diaphragmatic excursion than did those receiving plain drug.